Self inflicted stab with a knife: An unusual mode of penetrating brain injury - Qazi, Zeeshan; Ojha, Bal; Chandra, Anil; Singh, Sunil; Srivastava, Chhitij; Verma, Nishant; Patil, Tushar (Asian Journal of Neurosurgery, 2017)
Self-inflicted penetrating injuries have been very rarely described in the medical literature. We describe a middle-aged woman, who had driven a long knife inside her skull with the help of a brick. She had done this to get relief from chronic headache, which was troubling her for 10 years. Patient was hemodynamically stable and had Glassgow Coma scale score of 15. She was immediately operated to remove the knife and evacuate the acute subdural hematoma. Patient made a steady postoperative recovery. Psychiatric and neurological evaluation in the postoperative period revealed features of mixed anxiety and depressive disorder with migraine, for which she was started on treatment. Management of such cases needs a team approach with inputs from neurosurgeon, neurophysician and psychiatrist.
Keywords: Head injury; headache; penetrating; stab; self-inflicted